Individual and Collective Self-Efficacy Beliefs on Climate Change—Development of an Item-Based Instrument (SEB-CC) and Exploration of the Factorial Structure Among School Students and Future Geography Teachers - Schubert, Jan Christoph; Velling, Hanna; Höhnle, Steffen; Hofmann, Anna (Journal of Geography Education, 2024)
Self-efficacy beliefs are an important predictor of environmental actions. However, to date, there has been a lack of reliable and valid instruments for assessing individual and collective self-efficacy beliefs on the crucial topic of climate change. Therefore, items were developed and used with university students of geography (future geography teachers, n = 141) and students at the low end of secondary school (n = 154). After analyzing item characteristics, the factorial structure was examined. The results show different latent structures for the two groups, though each can be meaningfully interpreted. Thus, initial instruments are now available for further research.